Оценка эффективности применения лечебно-профилактического комплекса при лечении генерализованного пародонтита у мужчин зрелого и пожилого возраста = Evaluating the effectiveness of therapeutic and prophylactic complex in the treatment of generalized periodontitis in men mature and elderly - A. E. Korneychuk (Kazimierz Wielki University, 2016)
Korneychuk A. E. Оценка эффективности применения лечебно-профилактического комплекса при лечении генерализованного пародонтита у мужчин зрелого и пожилого возраста = Evaluating the effectiveness of therapeutic and prophylactic complex in the treatment of generalized periodontitis in men mature and elderly. Journal of Education, Health and Sport. 2016;6(3):200-210. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50541 http://ojs.ukw.edu.pl/index.php/johs/article/view/3490   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 20.03.2016. Accepted: 23.03.2016.     ОЦЕНКА ЭФФЕКТИВНОСТИ ПРИМЕНЕНИЯ ЛЕЧЕБНО-ПРОФИЛАКТИЧЕСКОГО КОМПЛЕКСА ПРИ ЛЕЧЕНИИ ГЕНЕРАЛИЗОВАННОГО ПАРОДОНТИТА У МУЖЧИН ЗРЕЛОГО И ПОЖИЛОГО ВОЗРАСТА EVALUATING THE EFFECTIVENESS OF THERAPEUTIC AND PROPHYLACTIC COMPLEX IN THE TREATMENT OF GENERALIZED PERIODONTITIS IN MEN MATURE AND ELDERLY   Корнейчук А. Е. Korneychuk A. E.   Государственное учреждение «Днепропетровская медицинская академия МЗ Украины» State Institution «Dnipropetrovsk Medical Academy of the Ministry of Health of Ukraine»   Summary. The article presents the results of evaluation of the effectiveness of therapeutic and prophylactic complex including adaptogens, antioxidants, vitamins and minerals, in the treatment of generalized periodontitis in males of the second half of the mature and elderly. The high efficiency of the proposed parodont complex treatment, as evidenced by the improvement of the hygienic condition of the oral cavity and the reduction of inflammation in the periodontal tissues in next term observation.   Key words: generalized periodontitis, aggravation, therapeutic and preventive complex, mature men and elderly.   Резюме. В статье представлены результаты оценки эффективности применения лечебно-профилактического комплекса, включающего адаптогены, антиоксиданты, витамины и минералы, при лечении генерализованного пародонтита у мужчин второй половины зрелого и пожилого возраста.  Показана высокая пародонтопротекторная эффективность предложенного комплексного лечения, что подтверждается улучшением гигиенического состояния полости рта и уменьшением воспалительного процесса в тканях пародонта в ближайшие сроки наблюдения.   Ключевые слова: генерализованный пародонтит, обострение, лечебно-профилактический комплекс, мужчины зрелого и пожилого возраста.   Резюме. У статті представлені результати оцінки ефективності застосування лікувально-профілактичного комплексу, що містить адаптогені, антиоксиданти, вітаміни і мінерали, при лікуванні генералізованого пародонтиту у чоловіків другої половини зрілого та похилого віку. Показана висока пародонтопротекторна ефективність запропонованого комплексного лікування, що підтверджується поліпшенням гігієнічного стану порожнини рота й зменшенням запального процесу в тканинах пародонта у найближчі терміни спостереження.   Ключові слова: генералізований пародонтит, загострення, лікувально-профілактичний комплекс, чоловіки зрілого та похилого віку.